Evidence for prolate-oblate shape coexistence in the odd- A Br38 3573 nucleus - Bhattacharya S.; Trivedi T.; Mukherjee A.; Negi D.; Singh R.P.; Muralithar S.; Jehangir S.; Bhat G.H.; Nazir N.; Sheikh J.A.; Rather N.; Palit R.; Nag S.; Rajbanshi S.; Chakraborty S.; Kumar S.; Raju M.K.; Parkar V.V.; Choudhury D.; Kumar R.; Bhowmik R.K.; Pancholi S.C.; Jain A.K. (My University, 2025)
The excited states in Br73 nucleus have been investigated through the fusion evaporation reaction Cr50(Si28, αp)Br73 at a beam energy of 90 MeV using the Indian National Gamma Array. The γ-γ coincidence technique has been used to add eight new γ-ray transitions in the level scheme. The mixing ratio of ΔI=0 (mixed with E2 and M1) transitions have been determined using angular distribution and RDCO-polarization measurement. The half-life of the 9/2+ isomeric state has been measured to be τ1/2=52(2) ns from the variation in the intensity of delayed γ-ray transition as a function of coincidence time window. The two state mixing model calculations were performed to obtain the mixing amplitude, and mixing interaction of two different configurations of Br73. The calculated mixing amplitudes along with the deformations of two different configurations provide the monopole transition strength ρ2(E0) for Se, Br, and Kr isotopes in a semiempirical approach. These results support a prolate-oblate shape coexistence in the odd-ABr73 nucleus. The observed structural properties have been discussed in terms of projected shell model calculations. © 2022 American Physical Society.